2013
DOI: 10.1093/carcin/bgt033
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between lysine-specific demethylase 1 (LSD1) and histone deacetylases mediates antineoplastic efficacy of HDAC inhibitors in human breast cancer cells

Abstract: Our previous studies demonstrated that lysine-specific demethylase 1 (LSD1) and histone deacetylases (HDACs) closely interact in controlling growth of breast cancer cells. However, the underlying mechanisms are largely unknown. In this study, we showed that knockdown of LSD1 expression (LSD1-KD) by RNAi decreased mRNA levels of HDAC isozymes in triple-negative breast cancer (TNBC) cells. Small interfering RNA (siRNA)-mediated depletion of HDAC5 expression induced the most significant accumulation of H3K4me2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 41 publications
4
90
0
Order By: Relevance
“…Here, it may be critical to consider that histone modification and DNA methylation cooperatively regulate chromatin structure and gene activity. For example, loss of LSD1 mediated by shRNA is found to suppress HDAC mRNA expressions in breast cancer cells (33). We have also verified the reduced mRNA levels of HDAC1 and HDAC2 after LSD1 knockdown in BM HSPCs.…”
Section: Discussionsupporting
confidence: 59%
“…Here, it may be critical to consider that histone modification and DNA methylation cooperatively regulate chromatin structure and gene activity. For example, loss of LSD1 mediated by shRNA is found to suppress HDAC mRNA expressions in breast cancer cells (33). We have also verified the reduced mRNA levels of HDAC1 and HDAC2 after LSD1 knockdown in BM HSPCs.…”
Section: Discussionsupporting
confidence: 59%
“…A role for elevated expression of LSD1 has been implicated in tumorigenesis in various cancers including breast cancer (3, 59). Studies from our and other laboratories consistently showed that inhibition of LSD1 hindered proliferation of breast cancer cells (6, 8, 10). Lim et al reported that LSD1 is highly expressed in ER-negative breast cancers (6).…”
Section: Introductionsupporting
confidence: 54%
“…Preclinical studies also indicate a synergistic antitumor effect of HDACi with other epigenetic-targeted drugs, such as lysine-specific histone demethylase inhibitors (Vasilatos et al 2013; Fiskus et al 2014). These observations are consistent with recent findings that broad-acting HDAC inhibitors have minimal effect on promoter acetylation, but rather they promote H3K27 trimethylation, a silencing-associated histone modification (Halsall et al 2015).…”
Section: Clinical Landscape Of Hdac Inhibitors In Cancer Therapymentioning
confidence: 99%